Бытье Михаила Прасолова: повесть / Вадим Рыжаков - Рыжаков Вадим Степанович (Современник, 1990)
Экземпляры: аб. (1990) / Инвентарный номер: 31451 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 93 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44